Effects of osmotic dehydration on mango (Mangifera indica L. cv. Carabao) at different ripening stages - Lewis, Xena Eunice D.
This study aimed to determine the effects of osmotic dehydration on mango (Mangifera indica L. cv. Carabao) at different ripening stages. The physico-chemical characteristics (color L*a*b* values, total soluble solids (°Bx), titratable acidity (%), and pH) of mango during ripening for 10 days after harvest were monitored. Mangoes at 6 different ripening stages (1, 2, 3, 4, 8, and 10 days after harvest) were prepared into 10x10x10mm cubes and subjected to osmotic dehydration in 65°Bx sucrose solution at 35°C for 6 hours. The % moisture content (dry basis) and TSS were determined at 0, 1, 2, 3, 4, 5, and 6 hours of osmotic dehydration and used to calculate for solid gain (SG), water loss (WL), and dehydration efficiency index (DEI). Lastly, the consumer acceptability of cabinet dried mango with osmotic dehydration pre-treatment was conducted. Ripening was characterized by development of a yellow-orange color in the mango flesh, increase in TSS content (9.80 ± 0.35 % to 18.17 ± 0.40%), pH (2.72 ± 0.12 to 4.56 ± 0.04) and TSS to TA ratio (3.30 ± 0.37 % to 108.86 ± 11.48 %); and decrease in TA (2.99 ± 0.22% to 0.17 ± 0.02%). Significant differences (p<0.05) for TSS, solid gain, water loss and dehydration efficiency index (DEI) values were observed after osmotic dehydration at different ripening stages, which indicated that ripening stage of mango affected the final quality of osmotically dehydrated product. Consumer acceptability of cabinet dried mango with osmotic dehydration pre-treatment suggested that product desirability increased with ripening.